2016
DOI: 10.1017/gmh.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Service and Policy implication of substance use disorders among adolescents in juvenile correctional facilities in Lagos, Nigeria

Abstract: Background.Lack of relevant data has continued to militate against the development of policy and practice toward identification and treatment of alcohol/substance abuse among adolescents coming in contact with the juvenile justice system in Nigeria. This study aims to provide such data, including its policy/practice implications.Methods.One hundred and seventy eight (178) adolescents, who are representative of adolescents within the youth correctional services of Lagos jurisdiction, were interviewed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Even before independence, mental health disorders associated with the abuse of alcohol and other drugs were reported (Lambo, 1960). Since then, studies have reported increased use of a wide variety of drugs among different populations (Atilola et al, 2016;Dumbili, 2020;Gureje et al, 2007;Mechanovic et al, 2020). Results of the nationwide survey conducted in 2017 showed that cannabis (14.4%) is the most commonly used illicit drug in the country followed by opioids (4.7%) and codeine-based cough syrup (2.4%) (United Nations Office on Drugs and Crime, 2018).…”
Section: Drug Use and Treatment In Nigeriamentioning
confidence: 99%
“…Even before independence, mental health disorders associated with the abuse of alcohol and other drugs were reported (Lambo, 1960). Since then, studies have reported increased use of a wide variety of drugs among different populations (Atilola et al, 2016;Dumbili, 2020;Gureje et al, 2007;Mechanovic et al, 2020). Results of the nationwide survey conducted in 2017 showed that cannabis (14.4%) is the most commonly used illicit drug in the country followed by opioids (4.7%) and codeine-based cough syrup (2.4%) (United Nations Office on Drugs and Crime, 2018).…”
Section: Drug Use and Treatment In Nigeriamentioning
confidence: 99%
“…The available literature on the provision of culturally responsive comprehensive CAMH in LMICs is scarce. The available literature indicates that the majority of the ongoing child and adolescent research in LMICs has been aimed at identifying the burden of emotional, cognitive, and behavioral problems; needs related to resources; and the availability of resources for developing and implementing mental health programs in schools [ 6 , 9 , 42 45 ]. The scarcity of literature in this field supports the need for further studies that focus on developing culturally responsive mental health intervention programs.…”
Section: Introductionmentioning
confidence: 99%
“…The return on investment of early identi cation and intervention programs, such as SBMHP, has also been recognized [37][38]. These include reducing crime, raising earnings, and promoting education [37][38][39][40][41][42][43][44][45][46][47][48][49]. For instance, early mental health interventions, especially during adolescence, have been associated with prevention of lifetime disability for most people with mental health disorders [38].…”
Section: Introductionmentioning
confidence: 99%